The Role of 64/128-Slice Multidetector Computed Tomography to Assess the Progression of Coronary Atherosclerosis - Ayad, Sherif W (Clin Med Insights Cardiol, 2015)
OBJECTIVES: We studied the progression of coronary atherosclerosis over time as detected by multidetector computed tomography (MDCT) in relation to risk factors and plaque composition. BACKGROUND: Studies using MDCT are limited to the assessment of the degree of stenosis without taking into consideration the plaque composition that is seen by MDCT. METHODS: This study included 200 patients, complaining of chest pain and referred to do 64/128-contrast–enhanced MDCT for the second time, and both studies were retrieved and evaluated for the presence of plaque, plaque type, vessel wall remodeling, percent area, and diameter stenosis and compared in both studies. Plaque progression over time and its association with risk factors were determined. RESULTS: We included 200 patients, and 348 plaques were detected by 64/128 MDCT. The duration between follow-up and baseline studies was 25.9 ± 19.2 month. In all, 200 plaques showed progression (57.47%), 122 were stable (35.06%), and 26 regressed (7.47%). In longitudinal regression analysis, the presence of history of diabetes mellitus and dyslipidemia and the absence of intraplaque calcium deposits were independently associated with plaque progression over time (P < 0.0001). CONCLUSION: Coronary plaque burden of patients with chest pain and no history of acute coronary syndrome significantly increased over time. Progression is dependent on plaque composition and cardiovascular risk factors. Larger studies and longer follow-up period are needed to confirm the determinant factors for plaque progression.